Et in Arcadia Ambasz
Cinco proyectos del arquitecto Emilio Ambasz. Contiene: Schlumberger Research Laboratories, Austin, Texas. Houston Center Plaza, Housto, Texas. San Antonio Botanical Conservatory, San Antonio, Texas. Addition to the New Orleans Museun of Art, New Orleans, Louisiana. Celestial Gardens, Houston, Texas.
Keywords: AMBASZ, EMILIO; LABORATORIOS; CENTROS DE INVESTIGACION; PLAZAS; ESTADOS UNIDOS; TEXAS; HOUSTON; NUEVA ORLEANS; JARDINES BOTANICOS; MUSEOS; MUSEOS DE ARTE; INVERNADEROS